The Activity of Notika Leaves (Archboldiodendron calosericeum Kobuski) Against Tumors Necrosis Factor Alpha (TNF-α) Levels in Rats - Nuralifah Nuralifah; Parawansah Parawansah; Fadhliyah Malik; Nining Yulianti (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2022)
Background: Inflammation is a response process to tissue injury and infection. The inflammatory response causes the release of pro-inflammatory mediators such as IL-1, IL-6 and TNF-α which are the main cytokines in the acute inflammatory response. Plants that have the potential to be anti-inflammatory are notika leaves (Archboldiodendron calosericeum Kobuski). Purpose: This research was conducted to evaluate the anti-inflammatory activity of the ethanol extract of notika leaves against the levels of Tumor Necrosis Factor Alpha (TNF-α) in Wistar rats. Methods: The study used a post test only control group design. Rats were divided into five groups consisting of a positive control (diclofenac sodium), three extracts (100, 200 and 300 mg/kg BW) and Teeee carragenantrol gopre roups that are inlaporkan dari tanaman ketapang dalam spewa yang dilaporkan pada besar, dll –lar.negative control (NaCMC 0.5%). In vivo tests were carried out by induction of inflammatory using carragenan, administering preparations and measuring TNF-α levels using the ELISA method. Data were analyzed using the One Way ANOVA test. Results: The results showed that the mean levels of TNF-α in the positive control group (0.475 ng/L), negative control (0.816 ng/L), extract dose 100 mg/kgBW (0.67 ng/L), extract dose 200 mg/kgBW (0.7285 ng/L) and extract dosage of 300 mg/kgBW (0.7785 ng/L). Conclusion: The study concludes that the ethanol extract of notika leaves has anti-inflammatory activity against the levels of Tumor Necrosis Factor Alpha (TNF-α) in Wistar rats based on the reduction in levels with negative control and optimum dose was 100 mg/kgBW.